Editorial on “Bone remodeling in acetabular reconstruction using a Kerboull-Type reinforcement device and structural bone-grafting in total hip arthroplasty” - Iwase, Toshiki (Annals of Joint, 2017)
The article entitled “Bone Remodeling in Acetabular Reconstruction Using a Kerboull-Type Reinforcement Device and Structural Bone-Grafting in Total Hip Arthroplasty” (1) was reviewed in detail. In primary or revision total hip arthroplasty, acetabular bone loss is one of the challenging conditions to place the acetabular component at the original acetabular region. Although recent advance of ultra-porous coated metal acetabular shell or augment implants may influence the surgeons’ decision making at the time of pre-operative planning for such technically demanding conditions, we have to recognize that the most important concept of total hip arthroplasty is to place the hip rotation center at around the anatomical position with preserving the bone stock of the hip joint.